Application of a validated algorithm to estimate the effectiveness and cost of biologics for rheumatoid arthritis in the US pharmacy benefit manager context - Wu N; Bhurke S; Shah N; Harrison DJ (Dove Medical Press, 2015)
Ning Wu,1 Sharvari Bhurke,1 Neel Shah,2 David J Harrison2 1Health Economics and Epidemiology, Evidera, Lexington, MA, USA; 2Amgen Inc., Thousand Oaks, CA, USA Background: Several biologic medicines are available to treat rheumatoid arthritis (RA), and they differ in administration method (subcutaneous or intravenous [IV]). We analyzed a pharmacy benefit manager database to estimate claims-based, algorithm-determined effectiveness and cost per effectively treated patient for biologics used to treat RA. Methods: We analyzed the Medco Health Solutions pharmacy benefit manager database to identify patients with one or more claims for a biologic used to treat RA from 2007 to 2012. The first observed claim defined the index date, the previous 180 days were the pre-index period, and follow-up was 365 days after the index date. Effectiveness of a biologic was determined by a validated, published algorithm designed for use in claims database analyses. Cost per effectively treated patient as determined by the algorithm was calculated as the total annual cost of the biologic therapy divided by the number of effectively treated patients. Analyses were conducted for subcutaneous, IV, and individual biologics. Results: The analysis population was 1,090 patients (subcutaneous: 785, IV: 305; etanercept: 440, adalimumab: 345, infliximab: 201, abatacept: 104). The mean age was 49.7±9.4 years, and 78% of the patients were female. Effectiveness according to the algorithm was higher in subcutaneous (36%) versus IV biologics (23%; P<0.001), and in etanercept (36%) versus infliximab (22%; P<0.001) and versus abatacept (24%; P=0.02). Etanercept and adalimumab were similar (35%; P=0.77). The cost per effectively treated patient according to the algorithm was $64,738 for subcutaneous biologics, $80,408 for IV biologics, $62,841 for etanercept, $67,226 for adalimumab, $90,696 for infliximab, and $62,303 for abatacept. Conclusion: Effectiveness according to a validated, claims-based algorithm was higher in subcutaneous versus IV biologics. Cost per effectively treated patient according to the algorithm was approximately $16,000 less in subcutaneous versus IV biologics. Keywords: biologic medications, claims-based algorithm, pharmacy benefit management